Kualitas Pola Makan Sebagai Faktor Risiko Karies Gigi Molar Pertama Permanen Pada Anak Sekolah Dasar Di SDN 55 Gedong Tataan - Sutrio; Endang Sri Wahyuni; Anggun Rusyantia; Yulia Novika J (Nutrition Department, Poltekkes Kemenkes Tanjung Karang, 2026)
Dental caries remains one of the most prevalent oral health problems among school-aged children globally, including in Indonesia. Poor dietary quality, characterized by high consumption of cariogenic foods and low intake of protective foods such as fruits and vegetables, is an important risk factor for dental caries, particularly in the first permanent molars. This study aimed to analyze the relationship between dietary quality and the incidence of first permanent molar caries among elementary school students at SDN 55 Gedong Tataan. A cross-sectional study was conducted from July to August 2025 involving 150 fourth- and fifth-grade students selected through total sampling. Dietary quality was assessed using a Food Frequency Questionnaire (FFQ) covering food diversity, fruit and vegetable intake, frequency of cariogenic food consumption, snacking habits, and meal regularity. Dental caries examination of the first permanent molars was performed clinically by dental health professionals. Data were analyzed using the Chi-Square test with a significance level of p < 0.05 and Odds Ratio (OR). Children with poor dietary quality had a significantly higher risk of developing first permanent molar caries compared to those with good dietary quality (OR = 3.21; p = 0.002). There is a significant relationship between dietary quality and the incidence of first permanent molar caries among elementary school children. Improving dietary quality may play a crucial role in preventing dental caries.